Phytochemical and Biological Studies on Usnea Orientalis and Rhododendron Campanulatum of Nepal - Joshi, Sushika; Bastola, Pradip (Journal of Nepal Chemical Society, 2013)
Phytochemical and biological screening of Usnea orientalis and Rhododendron campanulatum were carried out. The brine shrimp bioassay showed that the ethereal and methanolic extract of Usnea orientalis and the methanolic extract of Rhododendron campanulatum were biologically active. Antibacterial susceptibility studies of various extracts showed that the ethereal extract of Usnea orientalis and methanolic extract of Rhododendron campanulatum have antibacterial properties towards both gram positive and gram negative bacteria. Two major constituents usnic acid and diffractaic acid from the ethereal extract of Usnea orientalis have been isolated and identified by their melting points, Co-TLC| and 1H-NMR spectra comparison with authentic samples. The other two compounds viz. atranorin and eumitrin have been identified by Co-TLC and melting points comparison with the authentic samples. Diffractaic acid was isolated from Usnea orientalis. Usnic acid showed inhibition towards gram positive bacteria i.e. S. aureus. The brine shrimp bioassay of pure isolated compounds showed that usnic acid, diffractaic acid and atranorin were biologically and pharmacologically active.DOI: http://dx.doi.org/10.3126/jncs.v30i0.9382Journal of Nepal Chemical Society Vol. 30, 2012 Page: 118-122 Uploaded date: 12/20/2013